Edukasi Pengembangan Usaha UMKM Warung Manisan Mak Susi Di Desa Air Periukan - Dania, Rahma (Universitas Dehasen Bengkulu, 2024)
UMKM are one of the things that affect the rate of economic growth. This community service was carried out regarding the socialization of business development in the UMKM sweet stalls of Ibu Susi. The internal development of the sweet shop business uses initial capital with personal savings, innovates for production, expands the marketing network, and completes its business facilities and infrastructure. However, some entrepreneurs are constrained by the increasing price of raw materials, limited human resources, have problems in capital, lack of facilities and infrastructure and lack of access to product marketing.